Analysis of Students’ Difficulties about Rotational Dynamic Topic Based on Resource Theory - Rahmawati, I.; Sutopo, S; Zulaikah, S. (Jurnal Pendidikan IPA Indonesia, 2017)
Students’ difficulties commonly are analyzed based on misconception theory. This paper aimed to analyze students’ difficulties on the rotational dynamic based on resource theory. The subject of research consisted of 108 first-year undergraduate students of Physics Education, State University of Malang. Firstly, the students were asked to solve 15 multiple-choice questions and gave open explanation. We then implemened a constant comparative method to identify and categorize some resources that students employed in solving several problems that most the students failed to respond correctly. The results indicated that the students had difficulties in solving problems related to the torque and the equilibrium of rigid body. The students’ difficulties were not merely caused by the lack of correct knowledge. Instead, they have the correct knowledge or resources but they activated them on inappropriate context. The students will be successfully used the resources to solve problems if they activated them in the right context.